1992
DOI: 10.3102/01623737014001021
|View full text |Cite
|
Sign up to set email alerts
|

Principals’ Instructional Leadership and School Performance: Implications for Policy Development

Abstract: Currently, many districts and states are pursuing reforms that focus on holding principals accountable for school performance. While effective schools research has established that strong principal leadership affects school academic achievement at least indirectly, this relationship is more complex than originally thought. Personnel decisions about principal effectiveness made by educational policymakers or lay-controlled school site councils should be made only after careful consideration of research on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 28 publications
2
71
1
2
Order By: Relevance
“…The school effectiveness research of the last 20 years affirms the role of principals in school success (e.g., Austin and Reynolds 1990;Goddard 2001;Goddard et al 2004;Goldring and Pasternak 1994;Hallinger and Heck 1996;Heck and Marcoulides 1993;Heck 1992;Leithwood and Jantzi 1999;Leithwood and Montgomery 1986;Louis et al 1996;Marks and Louis 1997;Marks and Printy 2003;Sebring and Bryk 2000;Sergiovanni 1995;Shen 2005;Taylor and Valentine 1985) in general and in raising student achievement in particular (e.g., Leithwood et al 2004;Marzano et al 2005;Witziers et al 2003). In this study, we asked the following questions: Which streams of data do principals use?…”
Section: Methodsmentioning
confidence: 95%
“…The school effectiveness research of the last 20 years affirms the role of principals in school success (e.g., Austin and Reynolds 1990;Goddard 2001;Goddard et al 2004;Goldring and Pasternak 1994;Hallinger and Heck 1996;Heck and Marcoulides 1993;Heck 1992;Leithwood and Jantzi 1999;Leithwood and Montgomery 1986;Louis et al 1996;Marks and Louis 1997;Marks and Printy 2003;Sebring and Bryk 2000;Sergiovanni 1995;Shen 2005;Taylor and Valentine 1985) in general and in raising student achievement in particular (e.g., Leithwood et al 2004;Marzano et al 2005;Witziers et al 2003). In this study, we asked the following questions: Which streams of data do principals use?…”
Section: Methodsmentioning
confidence: 95%
“…Throughout the years, the so-called instructional role of the principal quite strongly emerged from the school effectiveness research (Goldring & Pasternack, 1994;Hallinger, Bickman, & Davis, 1990;Heck, 1992;Leithwood & Montgomery, 1986;Levine & Lezotte, 1990;Mortimore, Sammons, Stoll, Lewis, & Ecob, 1988;Sammons, Hillman, & Mortimore 1995). However, while some researchers found that school leadership matters, the empirical basis for the statement that educational leadership matters was rather weak (Murphy, 1988).…”
Section: Theoretical Framework: Principals' Impact On Processes and Omentioning
confidence: 97%
“…This research posited a relationship between strong instructional leadership and student academic performance (Bossert, Dwyer, Rowan, & Lee, 1982: Hallinger & Murphy, 1985, defining instructional leadership according to specific instruction-related dimensions of the job, including defining the school's mission, managing curriculum and instruction, and promoting a positive learning climate (Hallinger, 2003). Subsequent research and scholarship raised doubts about principals' general capacity and inclination to engage in this more active and directive form of instructionally focused leadership (Bossert et al, 1982;Heck, 1992), especially in secondary schools where teachers' command of their subject content typically surpasses that of their supervising principal. Further, more traditional notions of instructional leadership, emphasizing the principal's coordination and control of classroom instruction in heroic fashion, fueled these doubts (Heck, Larson, & Marcoulides, 1990).…”
Section: Instructional Leadershipmentioning
confidence: 98%
“…Recent research includes qualitative case studies of highly challenged, high-performing schools (Charles A. Dana Center, 1999;J. F. Johnson, Lein, & Ragland, 1998;Maden, 2001;Scheurich, 1998) and quantitative studies examining indirect leadership effects on student outcomes (Hallinger, Bickman, & Davis, 1996;Heck, 1992Heck, , 2000Heck, Larsen, & Marcoulides, 1990;Leithwood & Jantzi, 1999;Marks & Printy, 2003). In fact, an extensive review of evidence related to the nature and size of these effects concluded that, among school-related factors, leadership is second only to classroom instruction in its contribution to student learning (Leithwood, Louis, Anderson, & Wahlstrom, 2004).…”
Section: Principal Leadership and Student Performancementioning
confidence: 99%